2020
DOI: 10.4209/aaqr.2020.04.0185
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Experiments and Numerical Simulations on Airflow and Aerosols Deposition in Human Airways and the Role of Bioaerosol Motion in COVID-19 Transmission

Abstract: Determining the hotspots and deposition efficiencies (DEs) for aerosols in human airways is important for both research and medical purposes. The complexity of the human airways and the breathing process limit the application of in vitro measurements to only two consecutive branches of the human airway. Herein, in-depth information on in vitro experiments and state-of-the-art review on various computational fluid dynamics (CFD) applications and finite element methods on airflow and aerosol motion in both healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 132 publications
(263 reference statements)
1
48
0
1
Order By: Relevance
“…Recent studies have suggested that the severity of the COVID-19 epidemic may be closely related to climatic factors, including the UV radiation dose ( Babu et al, 2020 ; Sfîcă et al, 2020 ; Suhaimi et al, 2020 ). And the role of particulate matter (PM) and aerosol in COVID-19 transmission has been increasingly recognized ( Hsiao et al, 2020 ; Mutuku et al, 2020 ; Razzini et al, 2020 ). Severe COVID-19 outbreaks in some areas may be associated with lower UV radiation dose in those areas ( Sfîcă et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that the severity of the COVID-19 epidemic may be closely related to climatic factors, including the UV radiation dose ( Babu et al, 2020 ; Sfîcă et al, 2020 ; Suhaimi et al, 2020 ). And the role of particulate matter (PM) and aerosol in COVID-19 transmission has been increasingly recognized ( Hsiao et al, 2020 ; Mutuku et al, 2020 ; Razzini et al, 2020 ). Severe COVID-19 outbreaks in some areas may be associated with lower UV radiation dose in those areas ( Sfîcă et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“… 27 Other papers support the possible merging of contaminated aerosol with fine particulate in the atmosphere. 28–30 The concentration of fine particles has also been repeatedly recognised by other authors as an important cofactor causing higher mortality rates in heavily contaminated areas. 31 32 This study is aimed at searching for a possible association between the initial spread of COVID-19 in Italy, registered from the end of February to the first weeks of March 2020 (February 24th to March 13th), and the frequency of high daily average concentrations of PM, recorded before the lockdown, taking into account the lag period of the infection (February 9th to February 29th).…”
Section: Introductionmentioning
confidence: 88%
“… 114 , 115 The primary mechanisms of aerosol deposition in the lung include inertial impaction, gravitational sedimentation, and Brownian diffusion as well as, to a lesser extent, interception (applied to elongated aerosols such as fibers) and electrostatic precipitation (applied to charged aerosols). 112 , 114 , 116 , 117 …”
Section: Aerosol Deposition In the Lungmentioning
confidence: 99%